2017
DOI: 10.3390/cancers9070081
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Core Non-Homologous End Joining Factors in Carcinogenesis and Cancer

Abstract: DNA double-strand breaks (DSBs) are deleterious DNA lesions that if left unrepaired or are misrepaired, potentially result in chromosomal aberrations, known drivers of carcinogenesis. Pathways that direct the repair of DSBs are traditionally believed to be guardians of the genome as they protect cells from genomic instability. The prominent DSB repair pathway in human cells is the non-homologous end joining (NHEJ) pathway, which mediates template-independent re-ligation of the broken DNA molecule and is active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 241 publications
(276 reference statements)
2
88
0
1
Order By: Relevance
“…A line of evidence shows that Ku protein expression is increased in tumor cells versus normal cells in gastric and colorectal cancer [33,34]. The same correlation has been established between DNA-PKcs overexpression and carcinogenesis in prostate, lung, colorectal, esophageal and gastric cancer [31]. It can be postulated that predominance of an error-prone pathway such as NHEJ, may inhibit the accurate HR pathway and drives genomic instability.…”
Section: Nhej and Carcinogenesismentioning
confidence: 80%
See 4 more Smart Citations
“…A line of evidence shows that Ku protein expression is increased in tumor cells versus normal cells in gastric and colorectal cancer [33,34]. The same correlation has been established between DNA-PKcs overexpression and carcinogenesis in prostate, lung, colorectal, esophageal and gastric cancer [31]. It can be postulated that predominance of an error-prone pathway such as NHEJ, may inhibit the accurate HR pathway and drives genomic instability.…”
Section: Nhej and Carcinogenesismentioning
confidence: 80%
“…Moreover, it has been shown that an overactive DNA damage repair in cancerous cells is associated with poor prognosis for patient. An over-efficient DNA damage repair provokes resistance to DNA damaging agent and is a barrier to treatment responsivity of malignancies [31].…”
Section: Dna Damage Repair and Cancermentioning
confidence: 99%
See 3 more Smart Citations